2013
DOI: 10.1111/1346-8138.12330
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B irradiation increases the expression of inflammatory cytokines in cultured sebocytes

Abstract: Sebaceous gland hyperplasia and increased sebum secretion after irradiation of ultraviolet (UV)-B has been widely accepted. This study was performed to clarify expression of inflammatory cytokines after irradiating UV-B in cultured sebocytes. Reverse transcription polymerase chain reaction was performed to measure gene expression of inflammatory cytokines, including interleukin (IL)-1β, IL-6, IL-8 and tumor necrosis factor-α, in cultured sebocytes after exposure to 40 and 70 mJ/cm(2) UV-B. Protein expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
2
23
1
4
Order By: Relevance
“…Another study reported that UVB irradiation markedly increased both cell proliferation and sebum production in cultured hamster sebocytes 15 . In contrast, our previous study demonstrated that UVB treatment did not increase sebum production in cultured human sebocytes 16 . In the present study, we examined the effects of treating cultured human sebocytes with UVA radiation, visible light, and infrared light.…”
Section: Discussioncontrasting
confidence: 70%
“…Another study reported that UVB irradiation markedly increased both cell proliferation and sebum production in cultured hamster sebocytes 15 . In contrast, our previous study demonstrated that UVB treatment did not increase sebum production in cultured human sebocytes 16 . In the present study, we examined the effects of treating cultured human sebocytes with UVA radiation, visible light, and infrared light.…”
Section: Discussioncontrasting
confidence: 70%
“…One of the major environmental factors affecting the skin is ultraviolet radiation (UVR). Both UVB and UVA have been reported to cause hyperplasia of the sebaceous gland, thickening of the stratum corneum , increase in sebum secretion and in the number of comedones . By targeting the cells and molecules within the skin, UVR triggers the production and release of antimicrobial peptides, activates the innate immune system and ultimately suppresses the adaptive cellular immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Both UVB and UVA have been reported to cause hyperplasia of the sebaceous gland, thickening of the stratum corneum, increase in sebum secretion and in the number of comedones. [112][113][114][115][116] By targeting the cells and molecules within the skin, UVR triggers the production and release of antimicrobial peptides, activates the innate immune system and ultimately suppresses the adaptive cellular immune response. As a consequence, skin microbiota may be altered and P. acnes may overcolonize the skin causing flares of acne.…”
Section: Acne Exposome Factorsmentioning
confidence: 99%
“…The selective photofilters present in Acne RA‐1,2 provide protection against UVB rays and allow partial penetration of UVA rays around 400 nm in wavelength. UVB rays have multiple detrimental effects on acne such as inducing inflammation, increasing proliferation of keratinocytes, and increasing production of sebum . In contrast, specific UVA wavelengths around 400 nm may have beneficial anti‐inflammatory actions in both acne‐prone and acne‐affected skin .…”
Section: Discussionmentioning
confidence: 53%
“…Patients were randomized to receive Acne RA‐1,2 (Meda Pharma [a Mylan company], Monza, Italy) or matching placebo for 8 weeks. Acne RA‐1,2 contains selective photofilters (ethylhexyl methoxycinnamate, 4‐methylbenzylidene camphor, ethylhexyl triazone, methylene bis‐benzotriazolyl tetramethylbutylphenol, titanium dioxide [nano]) to protect against UVB rays, which may worsen acne, while allowing partial penetration of UVA rays around 400 nm in wavelength, which may be of benefit in treating acne (Table ) . The other active ingredients in Acne RA‐1,2 target the principal pathogenic factors of acne (Table ).…”
Section: Methodsmentioning
confidence: 99%